Os efeitos do exercício físico sobre a criatividade em adultos saudáveis: uma revisão sistemática - CORRÊA JUNIOR, Anderson Levy Mardock (2021)
Objective: This study aims to understand the effects of exercise physical in the creativity of healthy adults. Method: Systematic Literature Review performed in nine electronic databases. Articles that met to the following eligibility criteria: a) healthy young adults, without disease or diagnosed disorders, aged between 18 and 59 years; b) physical exercise such as method of intervention, whether acute (single episode) or chronic (episodes repeated over days, weeks or months; c) the research presented creativity as a variable of interest, having been considered its different aspects based on in the definitions of divergent thinking and convergent thinking; d) present as comparison control group that does not perform physical exercise or perform any other interventions or comparison with the group's own baseline; e) articles published between 1990 and November 2020 f) published in Portuguese, English and Spanish. Twelve articles were included, nine of which randomized clinical trials and three assessed the acute effect of exercise in cross-over design studies. Results: Nine showed positive effects of physical exercise on some measure of the creativity process and only three studies failed to achieve positive effects arising from the exercise. In the evaluated articles, there was a tendency of physical exercise to influence the creativity process. Conclusion: Despite of all the attention given to this aspect of cognitive function, there is a need that future research, contemplate greater methodological rigor and better design of study in its scope, with a view to elucidating the dose-effect relationships between the exercise physical and creativity for the investigated public.